Flow-induced vibrations : classifications and lessons from practical experiences - Kaneko, S. (Shigehiko); Nakamura, T. (Tomomichi); Inada, Fumio; Kato, Minoru (Engineer); Ishihara, Kunihiko; Nishihara, Takashi; Mureithi, Njuki W.; Langthjem, Mikael A. (Engineering professional collection, 2014)
In many plants, vibration and noise problems occur due to fluid flow, which can greatly disrupt smooth plant operations. These flow-related phenomena are called flow-induced vibration. This book explains how and why such vibrations happen and provides hints and tips on how to avoid them in future plant design. The world-leading author team doesn't assume prior knowledge of mathematical methods and provides the reader with information on the basics of modeling. The book includes several practical examples and thorough explanations of the structure, the evaluation method.